2020
DOI: 10.1136/openhrt-2019-001181
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided antecubital vein approach for right heart catheterisation in a Brazilian tertiary centre

Abstract: ObjectiveAs a parallel to the radial approach for left heart catheterisation, forearm veins may be considered for the performance of right heart catheterisation. However, data regarding the application of this technique under ultrasound guidance are scarce. The current study aims to demonstrate the feasibility of right heart catheterisation through ultrasound-guided antecubital venous approach in the highly heterogeneous population usually referred for right heart catheterisation.MethodsData from consecutive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…6 Notably, our group has demonstrated high applicability of an ultrasound-guided antecubital approach in patients undergoing right heart catheterization. 7 Furthermore, our previously published experience has demonstrated that the ultrasound-guided upper limb approach has a high success rate and minimal immediate vascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…6 Notably, our group has demonstrated high applicability of an ultrasound-guided antecubital approach in patients undergoing right heart catheterization. 7 Furthermore, our previously published experience has demonstrated that the ultrasound-guided upper limb approach has a high success rate and minimal immediate vascular complications.…”
Section: Introductionmentioning
confidence: 99%